Identifying the Races of Meloidogyne Incognita Populations in Assam, India - Rimi Deuri; Prabhat Das; Debanand Das; B. N. Choudhury (Current Overview on Disease and Health Research Vol. 6, 2022)
The present investigation was carried out to identify the races of M. incognita infesting vegetable crop like tomato in Assam, India. Diagnosis of species and races of Meloidogyne has always been challenging due to highly similar morphologically across species, life stages in different habitats, variable host ranges, poorly defined boundaries among species, intraspecific variability, potential hybrid origin and polyploidy. Differential hosts are used to detect pathogenic variation within root-knot nematode isolates or species. Accurate and precise identification of Meloidogyne species is based on a combination of several methods viz., morphological characteristics and morphometrics, host preferences, biochemical and molecular techniques are all equally important.